Structure-properties relations in graphene derivatives and metamaterials obtained by atomic-scale modeling. Issue 14 (13th October 2019) - Maroudas, Dimitrios; Muniz, Andre R.; Ramasubramaniam, Ashwin
ABSTRACT: Recent findings of atomic-scale modelling studies are reviewed on graphene derivatives and metamaterials fabricated through chemical functionalization and/or defect engineering of graphene sheets. Results of molecular-statics and molecular-dynamics simulations according to a reliable bond-order potential, as well as first-principles density functional theory calculations are reviewed that have established useful structure-properties relations in two-dimensional materials, such as graphene nanomeshes (GNMs), electron-irradiated graphene, and interlayer-bonded twisted bilayer graphene. Quantitative relationships are established for the elastic moduli, mechanical properties, and thermal conductivity of GNMs as a function of the nanomesh porosity and the mechanical response of GNMs to uniaxial tensile straining is explored over the range of nanomesh porosities. The dependence of structural, mechanical, and thermal transport properties of electron-irradiated graphene sheets on the density of irradiation-induced defects is reviewed, highlighting an amorphization transition accompanied by a brittle-to-ductile transition and a transition in thermal transport mechanism beyond a critical defect concentration. The tunability of the electronic band structure, mechanical properties, and structural response to mechanical loading of graphene-diamond nanocomposite superstructures consisting of nanodiamond superlattices in interlayer-bonded twisted bilayer graphene also is demonstrated by precise control of the density and distribution of covalent interlayer C–C bonds.